A secreted ribonuclease effector from Verticillium dahliae localizes in the plant nucleus to modulate host immunity. (1st April 2022) - Yin, Chun‐Mei; Li, Jun‐Jiao; Wang, Dan; Zhang, Dan‐Dan; Song, Jian; Kong, Zhi‐Qiang; Wang, Bao‐Li; Hu, Xiao‐Ping; Klosterman, Steven J.; Subbarao, Krishna V.; Chen, Jie‐Yin; Dai, Xiao‐Feng
Abstract: The arms race between fungal pathogens and plant hosts involves recognition of fungal effectors to induce host immunity. Although various fungal effectors have been identified, the effector functions of ribonucleases are largely unknown. Herein, we identified a ribonuclease secreted by Verticillium dahliae (VdRTX1) that translocates into the plant nucleus to modulate immunity. The activity of VdRTX1 causes hypersensitive response (HR)‐related cell death in Nicotiana benthamiana and cotton. VdRTX1 possesses a signal peptide but is unlikely to be an apoplastic effector because its nuclear localization in the plant is necessary for cell death induction. Knockout of VdRTX1 significantly enhanced V. dahliae virulence on tobacco while V. dahliae employs the known suppressor VdCBM1 to escape the immunity induced by VdRTX1. VdRTX1 homologs are widely distributed in fungi but transient expression of 24 homologs from other fungi did not yield cell death induction, suggesting that this function is specific to the VdRTX1 in V . dahliae . Expression of site‐directed mutants of VdRTX1 in N. benthamiana leaves revealed conserved ligand‐binding sites that are important for VdRTX1 function in inducing cell death. Thus, VdRTX1 functions as a unique HR‐inducing effector in V. dahliae that contributes to the activation of plant immunity. Abstract : Verticillium dahliae ribonuclease VdRTX1 functions as an effector to modulate plant immunity.